Place smart, load hard - structural reinforcement of the trailing edge regions of a wind turbine blade strengthening the buckling resistance. (15th November 2022) - Haselbach, Philipp Ulrich; Chen, Xiao; Berring, Peter
Abstract: Local buckling is one of the key driving forces of trailing edge failure in composite wind turbine blades. This study demonstrated a significant stiffness increase by adding a minor amount of foam material to the trailing edge region of a wind turbine blade. The proposed 'place smart, load hard' concept is based on the understanding of the local buckling in the critical trailing edge regions and to place additional foam there, where the blade is prone to buckle. The effective placing of foam inserts is numerically demonstrated for different load scenarios and its superiority compared to an experimentally validated blade model without foam inserts. The proposed strengthening method can be used for both building new blades and retrofitting old blades with local buckling issues in the trailing edge regions.